1986
DOI: 10.1128/jcm.23.2.360-365.1986
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid profile analysis in epidemiological studies of animal Salmonella typhimurium infection in Japan

Abstract: Plasmid profiles were investigated in 65 isolates of SalmoneUla typhimurium derived from aninal outbreaks during the period of 1978 through 1983 in Japan. Incidence of plasmids, drug-resistance, and conjugative R plasmids were extraordinarily high in these isolates. This high incidence reflects the prophylactic and therapeutic use of antibiotics. Most isolates from diseased animals, cohabiting animals, and each farm showed the same or similar plasmid patterns. However, there was a difference in plasmid pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…To investigate whether strains isolated from different stages of animal production can be connected with and reisolated from cases of human salmonellosis, typing methods other than traditional biochemical tests, serotyping, and patterns of susceptibility to antimicrobial agents may offer considerable assistance (18). Plasmid profiles have previously been used to link cases of disease with the source of infection (9,12), and this is considered to be a rapid, inexpensive and reproducible epidemiological typing system, applicable to a variety of bacterial pathogens (1 8). After initial isolation from broiler parent stock, S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether strains isolated from different stages of animal production can be connected with and reisolated from cases of human salmonellosis, typing methods other than traditional biochemical tests, serotyping, and patterns of susceptibility to antimicrobial agents may offer considerable assistance (18). Plasmid profiles have previously been used to link cases of disease with the source of infection (9,12), and this is considered to be a rapid, inexpensive and reproducible epidemiological typing system, applicable to a variety of bacterial pathogens (1 8). After initial isolation from broiler parent stock, S .…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid screening has been used to distinguish between different clones of a serovar of S. enterica in common source infections in animals (12) and in humans (9). The aim of the present study was to investigate the presence of plasmids in S. berta isolated from Danish broilers.…”
mentioning
confidence: 99%
“…As essentially the same bla KPC‐2 environment (Variants 1a and 1b) was found in different species, we speculated that a unique plasmid could be responsible for such interspecies dissemination. However, a plasmid content analysis [18] of the 16 isolates harbouring Variants 1a and 1b showed a range of plasmid sizes (7–80 kb), with several isolates harbouring more than one plasmid (data not shown). In addition, a Southern blot analysis with a bla KPC probe showed that bla KPC‐2 was associated with plasmids of different sizes (data not shown).…”
mentioning
confidence: 99%
“…In addition to these so-called virulence plasmids, several other types have been detected in Salmonella strains isolated from human or animals, usually for epidemiologi-Correspondence to: R. Rotger, Departamento de Microbiologla II, Facultad de Farmacia, Universidad Complutense, E28040 Madrid, Spain. cal typing purposes [2][3][4]. Although some of these plasmids have been related to antibiotic resistance, and genes responsible for DNA repair have been detected in others [5], most of them remain as cryptic plasmids of unknown function.…”
Section: Introductionmentioning
confidence: 99%